A STUDY ON STUDENTS’ MOTIVATION IN STUDYING ENGLISH AS ENGLISH FOREIGN LANGUAGE (EFL) AT STIKES CENDEKIA UTAMA KUDUS - Husna, Arina Hafadhotul; Tri Murtini, Rahayu (English Education:Journal of English Teaching and Research, 2019)
English is studied as a second language and it has crucial role in every aspect, especially in educational aspect. In the millennial era, students not only use English in their real communication, but they also use it to communicate on several application or websites. English need to study by the students at the university level because it will skilled them for their future. This study attempts to know what kinds of motivation had by the students in studying English at STIKES Cendekia Utama Kudus. The design of this research is descriptive qualitative. It is conducted to find the students’ motivation in studying English; either student used extrinsic motivation or intrinsic motivation. The population in this research was all of the students who take an English Subject on even semester in the academic years 2018/2019, while the sample in this research was 139 students. The researcher used Likert Scale rating score as the instrument and also questionnaire which were adapted from Gardner’s Attitude or Motivation Test Battery (AMTB). The finding explained that extrinsic motivational level is higher than intrinsic motivational level. The extrinsic motivational level stands in point 4.14, while intrinsic motivational level stands in point 4.04. Although, total score of extrinsic motivational lever is higher than intrinsic motivational level, both of them are in a high level. This result showed that students have good motivation, both in Intrinsic and Extrinsic motivation. It will be useful for the lecturer to make learning English better on their future. Key Words; Intrinsic Motivation, Extrinsic motivation, EFL, AMTB